ASSESSMENT OF THE KNOWLEDGE AND ATTITUDE TOWARDS ANTIBIOTIC RESISTANCE AMONG PEOPLE RESIDING IN NAMUWONGO, MAKINDYE EAST DIVISION KAMPALA, UGANDA, A QUALITATIVE AND DESCRIPTIVE CROSS-SECTIONAL STUDY - Daniel Safari; Emilly Faith Atim; Isaac Ogwal; Bashird, Mwambi; Brenda Ann Nalubwama (Student's Journal of Health Research, 2023)
Background: There is an increasing global concern of Antibiotic resistance causing a serious threat to public health with estimated 700,000 deaths per year and it's estimated to increase to about 10 million deaths by 2050(WHO). The aim of this study was to assess the knowledge and attitude towards antibiotic resistance among people residing in Namuwongo, Makindye East Division, Kampala Uganda. Methodology: A qualitative and descriptive cross-sectional study among 178 randomly selected participants through a structured questionnaire. Results: Of the 178 respondents, majority of the respondents were females 125/178 (70.22%).137 (76.97)of residents agreed that missing an antibiotic dose contributes to antibiotic resistance (mean score of 2.62±0.74). 122 (68.54) respondents agreed that consumption of antibiotics without physician's prescription can contribute to antibiotic resistance. (mean score of 2.45±0.85).Majority of respondents agreed to antibiotic resistance is increasing (73.60%, Mean score 2.58±0.75). 135 (75.84) agreed that antibiotic resistance can be accelerated by the overuse of antibiotics.(mean score of 2.61±0.73). But 127 (71.35) also agreed that Antibiotics are effective for the treatment of both bacterial and viral infections (mean score of 2.56±0.75). . 93.82% agreed that the government should create more awareness of antibiotic resistance (Mean score 2.91±0.37).  Recommendations Each pharmacy should at-least have a basic  laboratory so that patients get tested before any prescription, this will curb the  unnecessary and wrong usage of antibiotics for illnesses  not caused by bacteria. Drug shops should strongly be advised only to dispense medicines especially antibiotics provided the buyer has a genuine prescription note from a medical doctor,this practise shall thereby reduce self medication that leads to irrational use of antibiotics in treatment of viral infection Conclusion:There was poor knowledge about the usage of antibiotics in treatment of viral infections. There is need for raising more awareness and education on antibiotic resistance, particularly on the proper antibiotics usage.